Determinants promoting and hindering physical activity in primary school children in Germany: a qualitative study with students, teachers and parents - Louisa Sell; Louisa Sell; Berit Brandes; Mirko Brandes; Hajo Zeeb; Hajo Zeeb; Heide Busse (Frontiers Media S.A., 2024)
BackgroundDeterminants affecting children's physical activity (PA) at an early age are of particular interest to develop and strengthen strategies for increasing the levels of children's PA. A qualitative study was conducted to investigate the views of primary school-aged children, their teachers and parents regarding barriers and facilitators to engage in PA.MethodsFocus groups were conducted separately with primary school children, parents and teachers in a city in Northern Germany between October 2021 and January 2022. The semi- structured focus groups with children and teachers took part in person within school, whereas the focus groups with parents took place online. Data were transcribed verbatim and analysed using thematic analysis. During analysis, the socio-ecological model was identified as useful to map the determinants mentioned and was consequently applied to organize the data.ResultsTeachers (n = 10), parents (n = 18) and children (n = 46) of five primary schools in Germany participated in the focus groups. Participants of the three groups identified similar barriers and facilitators of PA in primary school-aged children, ranging across all four layers of the socio-ecological model. The barriers encountered were the preferences of children for sedentary activities (individual characteristics), the preference of parents to control their child's actions (microsystem), a lack of financial resources from parents and long sitting times in class (mesosystem), and barriers related to rainy weather and Covid-19 restrictions (exosystem). Facilitators mentioned were the childrens' natural tendency to be active (individual characteristics), involvement and co-participation of parents or peers in engaging in PA, support provided by teachers and the school (microsystem), living in rural areas, having sufficient facilities and favorable weather conditions (exosystem).ConclusionA range of determinants promoting and hindering PA, ranging across all layers of the socio-ecological model were identified by children, parents and teachers in this study. These determinants need to be kept in mind when developing effective PA intervention programs for primary school-aged children. Future interventions should go beyond individual characteristics to also acknowledge the influence of childrens' social surrounding, including parents, peers and teachers, and the wider (school) environment.